A aquisição dos conectores escritos em língua espanhola por acadêmicos do curso de letras segundo a Teoria Holística da Atividade - Cerezer, Andressa (2010)
This work aims to investigate acquisition of connectors and the conceptual acquisition of these categories in the writing of foreign language undergraduate students. The students of a Language Undergraduate Course with habilitation in Portuguese and Spanish and their respective literatures from a private college in the central region of Rio Grande do Sul were submitted to a framework approach based on Holistic Theory Activity during the year of 2009 in which Process-Writing by White and Arndt (1991) was used. The activities with these students were organized in four sequential modules. In each module, a different textual genre was produced and then rewritten four times. For data analysis, Corpus Linguistics was used through computer tools in order to survey lexical-grammatical patterns in the corpus. In this study, the softwares used were WordSmith Tools, by Scott (1998), and the Semantic Mapper, by Richter (2009). The theoretical foundation was based on the following aspects: social interactionist theory by Vygotsky with emphasis on key concepts as mediation, internalization and Zone of Proximal Development (ZPD); Activity Theory; Holistic Theory Activity; Framework according to Holistic Theory Activity; Language acquisition and connectors acquisition. The results show that a consistent and strongly theoretically based framework approach as the Holistic Theory Activity allows the students to advance in the acquisition of connector as the involvement with the proposed methodology also advances. Therefore, it is believed that when the students experience a framework methodology in the undergraduate course they can gain useful experiences and concepts for their professional practice, since this knowledge will allow the future teachers to interfere in the ZPD of their students when necessary.